Education and the Role of Parents in Islam: Building a Drug-Free Generation - Silawati Silawati; Aslati Aslati; Muhlasin Muhlasin; Arisman Arisman; Rizka Sari; Iin Gusmana (AL-ISHLAH: Jurnal Pendidikan, 2025)
Drug abuse among adolescents poses a serious threat to individual well-being and family stability. Within the Islamic framework, parents play a central role as moral and spiritual guides in protecting their children from harmful behaviors. This study explores the role of Islamic parenting in preventing adolescent drug abuse through the lens of da'wah psychology. This research employed a qualitative method using a literature review approach. Relevant scholarly works on Islamic parenting, da'wah psychology, and drug prevention strategies were analyzed. Descriptive analysis was conducted to examine the interconnections between Islamic values, parenting practices, and adolescent behavior. Findings indicate that Islamic parenting, when grounded in religious teachings and moral development, serves as an effective preventive mechanism against drug abuse. The integration of da'wah psychology enhances parents' ability to communicate religious and ethical messages persuasively, fosters stronger emotional bonds, and supports the creation of a psychologically healthy home environment. Key elements such as early inculcation of Islamic values, wise supervision, positive role modeling, and active parental involvement in children’s lives contribute significantly to deterring adolescents from drug-related behavior. The study concludes that Islamic parenting, supported by principles of da'wah psychology, provides a holistic framework for drug abuse prevention. Strengthening parental awareness and engagement within this framework can help nurture a resilient, morally grounded younger generation.